Opportunities for improving water productivity using mobile drip irrigation - Oker, Tobias Ebong (Kansas State University, 2018)
The Ogallala aquifer has been important to agriculture in the U.S. High Plains for the past six decades. Groundwater from the aquifer helped turn the fertile soils of the region, large parts of which are semi-arid, into some of the most productive agricultural lands in the U.S. and the world. However, this agricultural success has come at a great cost to the aquifer. Today, as a result of drastic aquifer drawdown, well capacities in some regions of the High Plains are no longer sufficient to sustainably irrigate crops. In response to this growing problem, wide ranging efforts towards conservation of the Ogallala aquifer were formulated and implemented. One of these efforts is to further improve irrigation efficiency. Adaptation of microirrigation, an efficient method of irrigation, to center pivots is regarded by some as the next major step towards expanding the usage of microirrigation technology, and along with-it improving the efficiency in center pivot systems. Four studies were conducted as parts of this dissertation with the application of a four-span center pivot, installed at the Kansas State University’s Southwest Research and Extension Centre (SWREC) in Garden City, Kansas. The studies assessed the technical performance of Mobile Drip Irrigation (MDI) compared to Low Elevation Spray Application (LESA) and Low Energy Precision Application (LEPA). In the first study, the irrigation uniformity, application efficiency and seasonal irrigation uniformity of MDI were evaluated against those of LEPA and LESA. Two sets of MDIs, one with a dripper flow rate of 3.8 L/h, and another of 7.6 L/h, a LESA spray and LEPA bubbler were utilized. Potential differences in season-long irrigation uniformity between the devices were evaluated by analyzing a periodically acquired vegetative index data from aerial imaging. The results showed that MDI and LEPA were more efficient than LESA as indicated by their significantly higher coefficients of uniformity and higher application efficiencies. The second study evaluated soil water redistribution under MDI against those of LEPA and LESA. The effect of irrigation was found to be mostly limited to the top 60 cm of the soil profile for all the evaluated irrigation application technologies. MDI and LEPA showed the highest horizontal variation in water content, and water redistribution pattern of MDI was similar to LEPA. In the third study, the performance of MDI for corn production, in comparison to LESA and LEPA was conducted by comparing grain yield, water productivity, above ground biomass, leaf area index (LAI), and soil water content. In general, crop biophysical measurements under MDI were not significantly different from those under LEPA and LESA, and any marginal benefits of MDI were likely masked by rainfall. Hence, further evaluation of MDI is recommended under stringent water application conditions. The fourth study assessed MDI dripline spacing and length for different soil types.Isaya Kisekka
Keywords: Mobile Drip Irrigation; Center pivots; Ogallala; HYDRUS